Juridical Analysis of Judges' Considerations in Cancellation of Marriage Because Husband Likes the Same Sex (Study of Decision Number 176/Pdt.G/2019/PA.YK) - Hasyarania, Hasyarania; Heriyani, Endang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The ideal marriage is a marriage between a man and a woman who by nature have an attraction to the opposite sex. In the life of the community there are some men who have sexual orientation with fellow men, not to women as the opposite sex. The purpose of this study is to determine the judge's legal basis in annulling a marriage with a husband who is a same-sex lover (homosexual) in decision number 176/Pdt.G/2019/PA.YK. The type of research used is normative legal research, with research data in the form of secondary data consisting of primary and secondary legal materials. In addition, interviews were also conducted with judges who decided this case at the Yogyakarta Religious Court to complement secondary data. Based on the results of the analysis, it is concluded that the legal basis for the judge's consideration in annulling the marriage between a woman and her same-sex lover husband in case number: 176/Pdt.G/2019/PA.Yk, is the provisions of Article 72 paragraph (2) KHI along with the explanation of Article 72 paragraph (2) KHI concerning fraud as a reason for annulling marriage. The sexual disorder in the form of homosexuality submitted by the applicant as a reason for annulment can be accepted as fraud committed by the husband to the wife, because the husband deliberately concealed his sexual disorder.